(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2021)
The green projects and initiatives are an important source to harmonize the relationships between society and nature. We define green projects as eco-friendly activities. Due to large-scale environmental problems for the last seventy years, it is relevant to develop the conditions for implementing these projects and transferring them to new spheres and regions. However, green projects are not often financed by traditional ways i.e. budget and bank financing. Therefore, an alternative way of financing such as crowdfunding is widely used regarding social and green projects. Nowadays, there are a lot of studies concerning the impact of various factors on the success of crowdfunding projects. However, there are not enough investigations about the values underlying the green crowdfunding projects. The purpose of the article is to investigate the values underlying the green projects and their impact on the attraction of funding from people living around the world. We identified seven values associated with the concept of sustainable development. According to these values, we studied the abstracts of 390 green projects on the crowdfunding platforms using the hermeneutical analysis. Additional we studied the relationship between the values and the project localization. Our findings allow enhancing the project attractiveness for backers. Besides, this research allows the project authors and the owners of crowdfunding platforms to predict the project development.